Взаємовідносини земств та державної влади в 60–80–х рр. XIX ст. в контексті формування громадянського суспільства в Російській імперії (на матеріалах Харківської губернії) - Бакуменко, О.О. (Культура народов Причерноморья, 2013)
В статье рассмотрены основные тенденции взаимоотношений Харьковского губернского
земства с государственной властью на начальном этапе существования системы земского
самоуправления (1864–1880–х гг.) и взаимосвязь этих отношений с процессами формирования основ
гражданского общества в Российской империи. Рассмотрены основные вопросы общественно–
политического плана, выносимые Харьковским губернским земством на повестку дня и реакцию
представителей власти на них. Сделаны выводы о соответствии деятельности земства основным
функциям института гражданского общества. В статті розглянуто основні тенденції взаємовідносин Харківського губернського земства з
державною владою в умовах розвитку системи земського самоврядування на початковому етапі (1864 –
1880–ті рр.). Проаналізовано взаємозв’язок цих відносин з процесами формування засад громадянського
суспільства в країні. Розглянуто основні питання громадсько–політичного плану, що ставилися
Харківським губернським земством на порядок денний та реакцію представників державної влади на
них. Зроблено висновки щодо відповідності діяльності земства основним функціям інститута
громадянського суспільства. In the article the basic tendencies of mutual relations of the Kharkov province zemstvo with state
power on the initial stage of existence of the system of zemstvo’s self–government are considered.
Intercommunication of these relationships with the processes of forming of bases of civil society is analyzed. The
main questions of social and political plan, taken away by the Kharkov province zemstvo on an order–paper and
reaction of state power agents on them, are considered. Connection is analyzed between events in the Kharkov
zemstvo and all–Russian tendencies of relations of power and society. The special attention is spared activity of
the Kharkov province zemstvo in the field of expansion of public opinion, development of mass media, bringing
the representatives of the society to the discussion of questions of national value. Influence of authoritarian
mode is analyzed on the general processes of development the civil society in a country. Accordance social and
political activity of zemstvos is considered to the legal field of Russian Empire of the second half of the
nineteenth century. Conclusions about accordance activity of zemstvo the basic functions of the institute of civil
society are done.